What is Beyond Budgeting in Ukraine: idea, fashion or innovation? Empirical study about Beyond Budgeting model in Ukrainian academic and professional environments - Aksom, Herman (Universitetet i Nordland, 2015)
Masteroppgave i bedriftsøkonomi - Universitetet i Nordland, 2015